Promosi Barbershop “Barageh Cuts” Kota Padang - M.Luqvi Wahyudi; Defrizal Saputra (Jurnal Riset Rumpun Seni, Desain dan Media, 2024)
The increasing spread of Barbershop has led to competition in similar businesses where business owners are certainly required to be able to implement effective marketing strategies, one of which is by utilizing platforms that are often used today such as Instagram, Facebook, Tiktok and others. The method of designing the promotion of Barageh Cuts Barbershop located in Padang City uses the glass box method. Data collection in designing promotional videos uses observation and interview methods accompanied by documentation as data support. The data obtained during data collection was analyzed using the 5W+1H method. This promotional design aims to overcome these problems with the main media output is a promotional video with a cinematic video concept using a storyline so that the video does not only contain advertising offers or promotions, but also has moral and educational values. Supporting media used are member cards, posters, x-banners, aprons, t-shirts, totebags, mugs, and stickers. The feasibility test of promotional videos that have been carried out through several respondents received positive responses. The design of this promotional video is expected to help Barbershop Barageh Cuts in improving marketing strategies and ready to compete with similar businesses.